Multiplication Of Purple Sweet Potato Shoots From Katulampa Accession In Vitro Using BAP (Benzyl Amino Purine) - Bagas Elang Samudra; Yulianti , Fitri; Azmi, Kiki Kawakibi (Jurnal Agroekoteknologi Terapan, 2025)
Sweet potato germplasm is highly diverse, but maintaining it in the field requires considerable energy and funds. In addition, there are biotic and abiotic stresses. In vitro culture is an alternative that can be used to reduce the risk of losing sweet potato germplasm. Efforts to store the germplasm of purple sweet potato from Katulampa accession in vitro culture can be made by multiplication of shoots with the addition of BAP (Benzyl Amino Purine). This study aimed to determine the effect of adding cytokinin growth regulators, namely BAP, on the multiplication of sweet potato shoots. This research was conducted at the Advanced Laboratory of Agrotechnology, Gunadarma University Campus F7, Ciracas, from March to July 2021. This research method uses a completely randomized design with one factor, the concentration of BAP (0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, and 2 ppm). Each treatment was repeated 15 times, and 1 repetition consisted of 1 bottle containing 1 sweet potato plant explant. The parameters to be observed in this study were the time of appearance of shoots, shoot height, and the number of leaves. The results showed that adding BAP to the shoot multiplication of purple sweet potato from Katulampa accession in vitro did not significantly affect the time the shoots appeared, shoot height, and the number of leaves. Keywords: growth regulator, cytokinin, plant tissue culture Abstrak Plasma nutfah ubi jalar memiliki keragaman tinggi, akan tetapi dalam mempertahankan plasma nutfah di lapang perlu tenaga dan dana yang cukup besar. Selain itu terdapat cekaman biotik dan abiotik. Kultur in vitro menjadi alternatif yang bisa dilakukan untuk mengurangi risiko kehilangan plasma nutfah ubi jalar. Upaya penyimpanan plasma nutfah ubi jalar ungu aksesi Katulampa pada kultur in vitro dapat dilakukan dengan multiplikasi tunas dengan penambahan BAP (Benzil Amino Purin). Tujuan penelitian ini untuk mengetahui pengaruh penambahan zat pengatur tumbuh sitokinin yaitu BAP terhadap multiplikasi tunas ubi jalar ungu aksesi Katulampa. Penelitian ini dilaksanakan di Laboratorium Lanjut Agroteknologi, Kampus F7 Universitas Gunadarma, Ciracas pada bulan Maret sampai Juli. Metode penelitian ini menggunakan Rancangan Acak Lengkap (RAL) satu faktor yaitu konsentrasi BAP yaitu 0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, dan 2 ppm. Setiap perlakuan diulang sebanyak 15 kali dan 1 ulangan terdiri atas 1 botol yang berisi 1 eksplan. Parameter yang diamati pada penelitian ini yaitu waktu muncul tunas, tinggi tunas, dan jumlah daun. Hasil penelitian menunjukan pemberian BAP pada multiplikasi tunas ubi jalar ungu aksesi Katulampa secara in vitro tidak berpengaruh nyata terhadap waktu muncul tunas, tinggi tunas dan jumlah daun. Kata kunci : zat pengatur tumbuh, sitokinin, kultur jaringan